2001
DOI: 10.1037/0735-7028.32.6.642
|View full text |Cite
|
Sign up to set email alerts
|

Sense of community among school psychologists on an Internet site.

Abstract: A major challenge confronting psychologists is finding relevant professional development experiences. An Internet-based professional community is one approach to meeting this challenge. The authors investigated the development of such a professional community among school psychologists. Results from behavioral measures and questionnaires reflected a moderate to strong sense of community among the participants. The single best predictor of sense of community was the participants' perceptions that the Internet s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
0
10
0
2
Order By: Relevance
“…Mais, alguns estudos foram realizados em Comunidades Relacionais que abrangem uma grande área geográfica. Por exemplo, Sonn e Fisher (1996) entrevistaram 23 membros do The Colored South African Community a viver em Melbourne, Austrália, e Kruger et al (2001) avaliaram o SPC numa comunidade cibernauta de psicólogos educacionais. Obst et al (2002b) investigaram o SPC geográfico e relacional percepcionado por membros de um clube internacional de ficção científica, e encontraram que os membros sentiram, na sua generalidade, laços comunitários mais fortes à sua comunidade de clube do que à sua vizinhança, apesar do facto de muita da comunicação entre os membros do clube ser feita através da Internet.…”
Section: Comunidades Geográficas Comunidades Relacionais E Vizinhançaunclassified
“…Mais, alguns estudos foram realizados em Comunidades Relacionais que abrangem uma grande área geográfica. Por exemplo, Sonn e Fisher (1996) entrevistaram 23 membros do The Colored South African Community a viver em Melbourne, Austrália, e Kruger et al (2001) avaliaram o SPC numa comunidade cibernauta de psicólogos educacionais. Obst et al (2002b) investigaram o SPC geográfico e relacional percepcionado por membros de um clube internacional de ficção científica, e encontraram que os membros sentiram, na sua generalidade, laços comunitários mais fortes à sua comunidade de clube do que à sua vizinhança, apesar do facto de muita da comunicação entre os membros do clube ser feita através da Internet.…”
Section: Comunidades Geográficas Comunidades Relacionais E Vizinhançaunclassified
“…McKenna and Green (2002) found that the Internet provides a central location or meeting place for individuals who are unable to meet regularly with similar others at a single geographical location and that online social support networks are beneficial for those who experience social anxiety or loneliness and time restrictions. Several other studies examining social networks via the Internet have found strengthened social support for online participants (Barrera, Glasgow, McKay, Boles, & Feil, 2002;Kruger, Maital, Macklem, Shriberg, Burgess, & Kalinsky, 2001;McKenna & Green, 2002).…”
Section: Introductionmentioning
confidence: 91%
“…Just to mention a few, the term is employed by Dawson (2006) in relation to the student communication and by Rovai (2002), who developed a scale to measure sense of community within the classroom. The concept is also employed with reference to the school psychologists interactions (Kruger et al 2001), to the effects of computer use on the sense of community of high school pupils (Wighting 2006), or in relation to a particular type of university (Ferrari et al 2009). More specific to our paper, there are studies focusing on preschool teachers' sense of community (McGinty, Justice and Rimm-Kaufman 2008; Guo et al 2011).…”
Section: Theoretical Frameworkmentioning
confidence: 99%